2021
DOI: 10.1002/aelm.202000877
|View full text |Cite
|
Sign up to set email alerts
|

Epsilon‐Negative Carbon Aerogels with State Transition from Dielectric to Degenerate Semiconductor

Abstract: Aerogels with negative parameters have become a research hotspot since the discovery of negative Poisson's ratio and negative thermal expansion coefficient in aerogels. The negative parameters are originally brought up and studied in electromagnetic metamaterials, leaving a question that whether aerogels can be used to construct metamaterials with negative electromagnetic parameters. Here, the authors show that negative permittivity (epsilon‐negative) property can be achieved in carbon aerogels, and its value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…It can be seen in Figure e that the resistance of conductive laser-printed paper-reinforced aerogel decreases with an increase in printing time and laser energy density. The resistance of the samples does not strictly decrease with an increase in graphitization degree but is positively associated (Figure S8), which is in accordance with the previous study . Besides, the samples obtained under five different laser printing conditions all show negative temperature coefficient of resistance (TCR) from 20 to 80 °C.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…It can be seen in Figure e that the resistance of conductive laser-printed paper-reinforced aerogel decreases with an increase in printing time and laser energy density. The resistance of the samples does not strictly decrease with an increase in graphitization degree but is positively associated (Figure S8), which is in accordance with the previous study . Besides, the samples obtained under five different laser printing conditions all show negative temperature coefficient of resistance (TCR) from 20 to 80 °C.…”
Section: Resultssupporting
confidence: 89%
“…The resistance of the samples does not strictly decrease with an increase in graphitization degree but is positively associated (Figure S8), which is in accordance with the previous study. 47 Besides, the samples obtained under five different laser printing conditions all show negative temperature coefficient of resistance (TCR) from 20 to 80 °C. Sample 50%−10%−3s has the maximum TCR of about 0.19%•°C −1 (Figure S9).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Resistors were derived from the leakage current and the external electrodes. [50] As the fitted line from the equivalent circuit model shown, the Chi-square value was 3.2×10 -3 , 2.09×10 -2 and 1.72×10 -3 for PS/MWCNTs film with MWCNTs content of 6, 10 and 15 wt% respectively, indicating the model was effective and in good accordance with experimental results.…”
Section: Dielectric Properties Of Ps/mwcnts Filmssupporting
confidence: 63%
“…Negative permittivity behavior comes from the oscillation of free electrons in conductors, where free electrons do simple harmonic motion, making the direction of polarization electric field same to the external electrical field [20,21]. Moreover, it is further found that negative permittivity can also be realized by the inherent characteristics of the component materials in traditional percolative composites, where dielectric constant transfers from positive value to negative value with increasing filler content near percolation threshold [22][23][24][25][26] Fe was kept constant (70 %). when content of Fe particles was beyond the percolation threshold (about 75 % of Fe/coated-Fe), the permittivity undergoes a sudden change from positive to negative (about 500 to -100) [27].…”
Section: Introductionmentioning
confidence: 99%